Leptospira infection complicated by demyelinating disease: A case report - Chen, Shu-Xin; Han, Deng-Ke; Liu, Yin; Ye, Zhi-Hua; Lu, Kui; Xu, Biao; Mai, Hui-qiang (Frontiers in Neurology, 2022)
Leptospirosis is a zoonotic disease, found worldwide, that is caused by bacteria of the genus Leptospira. People can be infected with Leptospira if they come in direct contact with the urine of an infected animal. Leptospirosis may be associated with demyelinating lesions of the central nervous system. This case report describes a 66-year-old female patient who presented with fever and generalized aches and progressed to unconsciousness within a few hours of admission. Laboratory tests showed Leptospira infection, and brain magnetic resonance imaging revealed acute demyelinating lesions. The patient responded well to penicillin and intravenous methylprednisolone therapy. Leptospirosis presenting with acute disseminated encephalomyelitis is rare. In this patient, an interdisciplinary collaboration involving the neurologist, radiologist, and pathologist was crucial for diagnosis and management. Further studies are warranted to investigate whether there is a correlation between demyelinating lesions and leptospiral infection.